2005
DOI: 10.1024/0300-9831.75.5.341
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effects of Oral Vitamin E Supplement in Type II Diabetic Patients

Abstract: This triple-blind, placebo-controlled clinical trial was conducted to determine the effect of the vitamin E on fasting blood sugar (FBS), serum insulin, and glycated hemoglobin (GHb) in type 11 diabetic patients (NIDDM). A total of 100 patients, with no complications, aged 20-60 years old were chosen from those consulting the Isfahan Social Security Service Diabetes Clinic and divided randomly into two treated and placebo groups, and matched for age, sex, level of education, and occupation. The treated and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 0 publications
2
30
1
Order By: Relevance
“…We also demonstrated that the blood glucose is not considerably changed in test groups with vitamin E supplementation, this effect was well established by other works (Boshtam et al, 2005, Sena et al, 2008. But, the correlation between blood glucose level and the proliferation index of lymohocytes in response to both stimuli indicates that the capacity of diabetic lymphocytes to proliferate against bacterial mitogens reduced gradually.…”
Section: Discussionsupporting
confidence: 59%
“…We also demonstrated that the blood glucose is not considerably changed in test groups with vitamin E supplementation, this effect was well established by other works (Boshtam et al, 2005, Sena et al, 2008. But, the correlation between blood glucose level and the proliferation index of lymohocytes in response to both stimuli indicates that the capacity of diabetic lymphocytes to proliferate against bacterial mitogens reduced gradually.…”
Section: Discussionsupporting
confidence: 59%
“…Available experimental evidence in diabetic animals and humans showed that short-term supplementation with vitamins C and/or E decreased insulin levels(15, 26) and reduced CAM concentrations and oxidative stress. (27) , (28) To our knowledge, it is unknown whether the combination vitamins E, C and β-carotene can attenuate pre-disease processes of insulin insensitivity, elevated endothelial adhesion molecule levels and oxidative stress levels in a younger, overweight population who is at risk for disease.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Another major target of ROS is the inflammatorymediated transcription factor called NFkB. [45][46][47] During the inflammatory stage, wounded tissue secretes growth factors and cytokines for initiation of healing process. Neutrophils phagocytize cell debris and bacteria and gradually replace monocytes with macrophages.…”
Section: 41mentioning
confidence: 99%